Synthesis of Dichlorophenyl-, Cyanophenyl- and Quinolinyl-Substituted - E. Gutteridge, Clare; M. Curtis, Sean; W. Major, Joshua; A. Nin, Daniel; K. Bhattacharjee, Apurba; A. Nichols, Daniel; Gerena, Lucia (Letters in Organic Chemistry, 2015)
A series of ten new 2,3,6-substituted quinazolin-4(3H)-one derivatives (10a-j) were prepared from anthranilic acid (1) in a simple and economical path in a series of reactions and screened for their anticancer activity against pancreatic cancer cell line (PANC-1) using MTT assay. The results reveal that at concentration 100 µM/L, compounds 10b, 10f, 10g and 10h exhibited potential anticancer activity by inhibiting the growth of PANC-1 cells by >75% and remaining compounds showed moderate anticancer activity. The structural characterization of the synthesized compounds was elucidated by 1H & 13C NMR, LC-MS, FT-IR and elemental analysis. As potential anti-tumor agents, these new derivatives show promise for further research.
Keywords: 2-ethoxyphenylacetamide